Association between various breathing indexes during sleep and the Epworth Sleepiness Scale score in adults. Issue 48 (2nd December 2022) - Hsieh, Pei-Shan; Hwang, Sheng-Wei; Hwang, Shang-Rung; Hwang, Juen-Haur
Abstract : Some breathing indexes during sleep, including the apnea-hypopnea index, oxygen desaturation index, and oxygen saturation during sleep, can be recorded by overnight polysomnography. We aimed to investigate the association of various breathing indexes during sleep with the Epworth Sleepiness Scale (ESS) score in adults. We retrospectively collected the clinical and overnight polysomnography data of 2829 adults aged 20 years or older from November 2011 to June 2017. The association of various breathing indexes during sleep and ESS score was analyzed using univariate and multivariate logistic regression analysis for all adults (20–91 years), and in each sex and of body mass index (<26 kg/m 2 vs ≥26 kg/m 2 ). The mean ESS score was 6.2 (standard deviation = 4.3; range = 0–24) for all adults. After adjustment for age, sex, many common diseases, and health-related habits, apnea-hypopnea index, oxygen desaturation index, percentage of oxygen saturation below 90% during sleep, and percentage of oxygen saturation below 85% during sleep were significantly positively associated with ESS score in all adults, whereas mean oxygen saturation during sleep, minimal oxygen saturation during sleep, and awake oxygen saturation during sleep were significantly negatively associated with ESS score in all adults. In subgroup analysis, we found that the association between breathing indexes during sleep and ESS score was similar in both sex, but was significant in subjects of body mass index ≥ 26 kg/m 2 . All breathing indexes during sleep had significant positive or negative correlation with ESS score in all adults, especially in obese subjects.